2020
DOI: 10.3390/ijerph18010108
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between School Integration, Psychosocial Adjustment and Cyber-Aggression among Adolescents

Abstract: The aim of this study was to analyze the relationships between sociometric types in the classroom—rejected, preferred, neglected, controversial and average—and psychological discomfort, life satisfaction and cyber-aggression, based on the adolescent’s gender. 2398 adolescents of both sexes participated in the study (49.8% girls), aged between 12 and 18 years (M = 16.03, SD = 1.91). Multivariate analyses of variance were performed. The results showed significant relationships between sociometric types, life sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
(94 reference statements)
0
9
0
2
Order By: Relevance
“…Bullying is defined as a form of aggressive behavior, including the intent to harm interpersonal relationships; it is also characterized by an imbalance of power [7]. Traditional school bullying has expanded beyond the school environment and into the cyber realm, where cyberbullying is considered part of a relational context involving the perpetration of bullying and victimization [3,8,9]. Many adolescents are evolving these issues into more diverse and complex forms, including overlapping verbal and emotional harassment both online and offline by ostracizing specific targets in the cyber realm [5,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Bullying is defined as a form of aggressive behavior, including the intent to harm interpersonal relationships; it is also characterized by an imbalance of power [7]. Traditional school bullying has expanded beyond the school environment and into the cyber realm, where cyberbullying is considered part of a relational context involving the perpetration of bullying and victimization [3,8,9]. Many adolescents are evolving these issues into more diverse and complex forms, including overlapping verbal and emotional harassment both online and offline by ostracizing specific targets in the cyber realm [5,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This type of violence has traditionally occurred in educational centers, but in recent years it has transcended the physical boundary to include the virtual environment. The new kind of peer aggression based on the use of new technologies (cyberbullying) has generated great interest among researchers and professionals (Estévez et al, 2019;León-Moreno et al, 2020). Recent studies have found that victims of cyberbullying exhibit symptoms such as anxiety (Doumas & Midgett, 2021), depression (Zhang et al, 2020), suicidal ideation (Iranzo et al, 2019), antisocial behavior (Garaigordobil, 2017), and decreased academic performance (Alzamil, 2021).…”
mentioning
confidence: 99%
“…Compared to those who are appreciated by their peers, adolescents who feel rejected or disregarded are more likely to engage in passive-aggressive behavior, including cyber aggression. The odds are higher in girls than in boys [ 35 ].…”
Section: Discussionmentioning
confidence: 99%